Estimation of present-day strength of concrete for a 40-yearold building from non-destructive tests: A case study - Karmakar, Soubhagya; Dauji, Saha; Kshirsagar, Sandeep Shankar; Sahni, Satish Kumar; Bhargav, Kapilesh; Mahapatra, Kamalendu (Journal of Asian Concrete Federation, 2021)
Assessment of the present health of existing concrete structures is necessary, particularly for enhancing the life of the infrastructure facilities reaching the end of their design life. The codes stipulate establishment of site-specific correlation expressions to estimate the compressive strength of concrete from indirect non-destructive tests (NDT) such as rebound hammer or ultrasonic pulse velocity tests. However, in certain circumstances, requisite number of partially destructive (core) tests required for establishing the site-specific equations might not be feasible. In such scenario, selection of a suitable correlation expression from literature has to be performed in a rational way, as discussed in this article with a case study of a 40-year-old concrete building. From the study, it has been observed that for the limited number of direct tests, the Indian code stipulation resulted in higher characteristic strength of concrete as compared to the parametric estimation, which can be attributed to the assumption of Normal distribution and code stipulated (conservative) standard deviation value. In case of the indirect estimation cases, the parametric characteristic strength was pretty close to the corresponding non-parametric values indicating that the fitted distributions represented the strength values very well. Recommendations for the suitable correlation expression from literature applicable for estimation of equivalent strength from NDT for the structure, recommendation for characteristic compressive strength of concrete and the suggestions for accounting for the inaccuracies in estimated strength in subsequent structural re-analysis have been provided from the results of the study.